Synthesis and Characterization of Ni2+-doped SnO2 Powders - Loan, Trinh Thi; Ngoc Long, Nguyen (VNU Journal of Science: Mathematics - Physics, 2019)
In this study, SnO 2 :Ni 2+ powders with dopant contents ranging from 0.0 to 12 mol% were synthesized by sol-gel method. The samples were characterized by X-ray diffraction (XRD) Raman spectroscopy, energy-dispersive X-ray spectrometer (EDS) and photoluminescense (PL) spectra. The XRD analysis shows that the samples doped with low Ni- concentrations exhibited single SnO 2 crystalline phase, whereas the samples doped with high Ni- concentrations exhibited a mixture of SnO 2 and NiO phases. The latti ce parameters of the SnO 2 host were independent of Ni 2+ dopant content, while Raman mode positions were dependent on Ni 2+ dopant content. The PL spectrum of the undoped SnO 2 was characterized by the emission peaks due to near band edge (NBE) emission and the violet emission peaks associated with surface dangling bonds or oxygen vacancies and Sn interstitials.